Fatigue behaviour of titanium dental endosseous implants - Alessandro Scicutelli; Daniela Pilone; Ferdinando Felli (Fracture and Structural Integrity)
In this work two different titanium dental implants are analyzed in order to evaluate their mechanical strength. An ad-hoc designed experimental apparatus is prepared to test against fatigue these implants in a way that approximates as much as possible the actual stresses occurring during mastication motion. The results of these endurance tests are summarized in the form of Wohler-type diagrams showing the duration of a specific implant for different applied loads. These plots show a fatigue limit below which the implants could resist indefinitely. Other aspects of this research concern the influence of a potentially corrosive medium and the analysis of the deformation and failure of the specimens. During fatigue cycling, the titanium implants do not seem to be affected by a more aggressive environment, such as a saline solution. The analysis of the broken specimen allowed the crack initiation sites and the type of fracture propagation to be investigated in depth. In all the considered implants fatigue cracks were seen to initiate preferentially from sites in which the tensile stress concentration is the highest. The results of a finite element analysis performed on one of the specimens is in good agreement with the failure mode observed after the tests. The SEM fracture surface analysis shows a clear similarity between the fracture mode of the tested implants and of the actual implants broken after a certain operating period.